Attraction of domestic and external investment sources in regional development pattern of the East and Southeast Asian countries - Lazneva, Iryna (Skhid, 2013)
The paper reviews and examines the role of investments as one of important determinants of economic growth pattern of the East and Southeast Asian countries. Active participation of government and institutional specificity of the Asian economies facilitating capital investments and economic growth is stressed in the article.